Primary diffuse leptomeningeal gliomatosis predominantly affecting the spinal cord: case report and review of the literature. Issue 2 (1st February 2001) - Baborie, A; Dunn, E M; Bridges, L R; Bamford, J M
Abstract : Primary leptomeningeal gliomatosis is a rare, fatal neoplastic syndrome. A 71 year old man is reported on, who after a 2 month history of back stiffness, epigastric pain, and weight loss developed visual blurring. Cranial CT and MRI studies showed no leptomeningeal enhancement. Examination of CSF 10 weeks premortem showed an increase in protein and decrease in glucose but no malignant cells. He became increasingly confused and repeated CSF examination showed inflammation and a few suspicious cells but no definitive evidence of neoplasia. He died 7 months after onset of his initial symptoms. At postmortem meningeal whitening was seen at the base of the brain and over the spinal cord. Histology disclosed diffuse leptomeningeal gliomatosis (GFAP positive, cytokeratin negative) over the brain, optic nerves, and spinal cord without parenchymal involvement. No tumour was found in internal organs. The diagnosis of primary leptomeningeal gliomatosis was not evident after cranial CT and MRI and CSF examination premortem. Suspected cases need MRI scanning of the entire neuraxis and meningeal biopsy.